Biological rhythms of the liver - Anatol Panasiuk; Mirosław Tarasewicz; Albert Chodowiec; Anna Łokić; Kacper Gan (Clinical & Experimental Hepatology)
The biological rhythm is a fundamental aspect of an organism, regulating many physiological processes. This study focuses on the analysis of the molecular basis of circadian rhythms and its impact on the functioning of the liver. The regulation of biological rhythms is carried out by the clock system, which consists of the central clock and peripheral clocks. The central clock is located in the suprachiasmatic nucleus (SCN) of the hypothalamus and is regulated by signals received from the retinal pathway. The SCN regulates the circadian rhythm of the entire body through its indirect influence on the peripheral clocks. In turn, the peripheral clocks can maintain their own rhythm, independent of the SCN, by creating special feedback loops between transcriptional and translational factors. The main protein families involved in these processes are CLOCK, BMAL, PER and CRY. Disorders in the expression of these factors have a significant impact on the functioning of the liver. In such cases lipid metabolism, cholesterol metabolism, bile acid metabolism, alcohol metabolism, and xenobiotic detoxification can be significantly affected. Clock dysfunctions contribute to the pathogenesis of various disorders, including fatty liver disease, liver cirrhosis and different types of cancer. Therefore understanding circadian rhythm can have significant implications for the therapy of many liver diseases, as well as the development of new preventive and treatment strategies.